2010
DOI: 10.1182/blood-2010-02-267435
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of TRAIL-mediated megakaryocyte apoptosis to impaired megakaryocyte and platelet production in immune thrombocytopenia

Abstract: Recent in vitro studies provide evidence for autoantibody-induced suppression of megakaryocytopoiesis and show a reduction in megakaryocyte production and maturation in the presence of immune thrombocytopenia (ITP) plasma. Here, we present CD34 ؉ cells from healthy umbilical cord blood mononuclear cells cultured in medium containing thrombopoietin, stem cell factor, interleukin-3, and 10% plasma from either ITP patients or healthy subjects. The quantity, quality, and apoptosis of megakaryocytes were measured. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
52
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 45 publications
7
52
0
1
Order By: Relevance
“…[32][33][34] Platelet production can be affected by abnormalities at any stage of MK production. 30 The impact of ITP sera on MK production and differentiation from CD34 + cells has been evaluated previously, [8][9][10] while other work has assessed the effect of antiplatelet monoclonal antibodies 11 and drugdependent antiplatelet antibodies 12 on proplatelet formation. Previous work did not, however, fully examine the activity of antiplatelet IgG from ITP patients on terminal MK differentiation (proplatelet formation and platelet release).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[32][33][34] Platelet production can be affected by abnormalities at any stage of MK production. 30 The impact of ITP sera on MK production and differentiation from CD34 + cells has been evaluated previously, [8][9][10] while other work has assessed the effect of antiplatelet monoclonal antibodies 11 and drugdependent antiplatelet antibodies 12 on proplatelet formation. Previous work did not, however, fully examine the activity of antiplatelet IgG from ITP patients on terminal MK differentiation (proplatelet formation and platelet release).…”
Section: Discussionmentioning
confidence: 99%
“…8 In vitro studies showed that plasma from patients with ITP suppressed MK growth and/or maturation. 8,9 On the other hand, Yang and colleagues 10 reported that ITP plasma stimulated the production of MK, but impaired their differentiation and the production of platelets. In vitro, the capacity of MK to form proplatelets can be inhibited by monoclonal antibodies against CD41 and CD42b.…”
Section: Introductionmentioning
confidence: 99%
“…These data established the notion that activation of the extrinsic pathway promotes platelet shedding. Studies of the TNF-related apoptosis-inducing ligand (TRAIL), another death receptor ligand, have provided support for this model, suggesting that TRAIL can promote megakaryocyte maturation 31 , and that reductions in megakaryocyte apoptosis caused by decreased TRAIL expression might contribute to impaired thrombopoiesis in immune thrombocytopenia patients 32 .…”
mentioning
confidence: 99%
“…TNF-α can initiate the release of cytosolic Cyt-c, which leads to the activation of caspase-9, evidence that the cell death is mitochondria-dependent (Zhao et al, 2001;Utaisincharoen et al, 2009;Alvarez et al, 2011). Recent studies have suggested that TNF activates platelet caspases via TNF-R1 and demonstrated the correlation between the activation of platelets and thrombocytopenia (Piguet et al, 2002;Yang et al, 2010). As a result, TNF-α significantly induced the cytosolic release of Cyt-c, which contributes to gene and protein expression of caspase-3, meaning that cell death is associated with the mitochondria.…”
Section: Discussionmentioning
confidence: 99%